Facile fabrication of pH-responsive nanoparticles from cellulose derivatives via Schiff base formation for controlled release. (15th July 2019) - Peng, Xinwen; Liu, Peiwen; Pang, Bo; Yao, Yawen; Wang, Jiaxiu; Zhang, Kai
Graphical abstract: Novel pH-responsive nanoparticles as promising delivery system were designed and constructed using 2, 3-dialdehyde cellulose derivatives. The resulting nanoparticles showed adjustable loading capacity that was tuned by changing the ratio of oleylamine and amino-containing compounds. The loaded nanoparticles exhibited excellent pH-regulated release behaviors via the cleavage of Schiff base bonds in aqueous environment with various pH values. Highlights: Novel pH-responsive NPs are prepared using 2, 3-dialdehyde cellulose. Diverse amines can be introduced into cellulose backbone via Schiff base formation. NPs show adjustable loading capacities by changing the amounts of amines. NPs exhibit excellent pH-regulated release behaviors in aqueous environment. Abstract: A controllable drug delivery system demonstrates a promising tool for diverse biomedical applications. In this work, a group of amphiphilic macromolecules was designed and prepared via Schiff base reactions between 2, 3-dialdehyde cellulose (DAC) with oleylamine and amino-containing compounds. Benefiting from the self-assemble process of these amphiphilic macromolecules in the poor solvent, a group of novel pH-responsive nanoparticles (NPs) were facilely fabricated by using nanoprecipitation dropping technique. The high amount of aldehyde groups on DAC chains enabled immobilization of tunable amounts of amine compounds (up to 1.67 mmol/g) in the NPs. Furthermore, the Schiff base bonds in NPs allowed the efficient release of the drug in acidic tumor microenvironment by cleaving the Schiff base linkages. This study demonstrates the formation of a group of novel pH-sensitive and drug-loadable NPs, which provide a simple and efficient drug delivery system for the potential application for cancer treatment.